User Education and File Standards Best Options to Ensure Open Educational Resources are Truly Open - Patterson, Jordan (Evidence Based Library and Information Practice, 2020)
A Review of: Ovadia, S. (2019). Addressing the technical challenges of open educational resources. portal: Libraries and the Academy, 19(1), 79-93. https://doi.org/10.1353/pla.2019.0005 Abstract Objective – To describe common technical challenges of open educational resources (OERs) and recommend solutions. Design – Descriptive study. Setting – Online open educational resources in higher education. Subjects – Open educational resources. Methods – Drawing from the literature and his own experiences, the author explains the necessity of accepted standards of “openness” and describes the many ways OERs fail to meet these standards. The author also describes common technical challenges that impede openness, then proposes solutions to address these challenges. Main Results – Technical limitations often prohibit OERs from being truly open. Providers can design their resources to encourage reuse, redistribution, revision, and remixing. Three strategies for addressing technical challenges in OERs are user education, open file standards, and using Git to facilitate distributed version control. Conclusion – Git is a compelling option for distributed version control, but entails its own technical challenges. User education and established open file standards are the best strategies to ensure that OERs are open in both a legal and a technical sense. The article concludes with the author’s opinions about how OER directors may most realistically implement these solutions.